Literasi Numerasi dalam Pembelajaran Operasi Hitung Pecahan pada Peserta Didik Kelas 5 SDN 2 Ngambarsari Wonogiri Tahun Pelajaran 2021/2022 - Aisyah, Siti; Suryanti, Suryanti; Sukarno, Sukarno (Universitas Mathla'ul Anwar Banten, 2023)
The aims of this study were (1) to describe the implementation of numeracy literacy in learning fractional arithmetic operations for fifth grade students during the pandemic; (2) Explain the obstacles to implementing numeracy literacy in grade 5 students; (3) Describe the results of learning fractional arithmetic operations during implementing numeracy literacy in grade 5 students. This type of research uses a qualitative descriptive approach. The research was conducted at SD Negeri 2 Ngambarsari, Wonogiri Regency. The research subjects were all fifth grade students. The implementation of numeracy literacy was carried out through 3 (three) stages, namely the habituation stage, the development stage which is oriented towards understanding the basic concepts of mathematics and the last stage is the application stage of mathematical concepts. Obstacles to implementing numeracy literacy in grade 5 students, namely: students' low interest in reading, the mindset of teachers who only encourage but do not provide role models for reading habitually, limited facilities and infrastructure for numeracy literacy media. The teacher's obstacles are: the teacher's lack of understanding of the concept of numeracy literacy, so that during learning the teacher is not able to apply learning material in everyday problems, and constraints related to time, namely reduced learning time as a result of the policy to control the spread of Covid-19. Class V numeracy literacy skills in learning fractional arithmetic operations obtained 3 (three) categories, namely: first low level, second low level, and medium level. The ability of numeracy literacy in learning fractional arithmetic operations is strongly influenced by how often students encounter arithmetic operations questions.